2011
DOI: 10.1016/j.mimet.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR methods for quantitative monitoring of streptomycin and tetracycline resistance genes in agricultural ecosystems

Abstract: Antibiotic application in plant agriculture is primarily used to control fire blight caused by Erwinia amylovora in pome fruit orchards. In order to facilitate environmental impact assessment for antibiotic applications, we developed and validated culture-independent quantitative real-time PCR multiplex assays for streptomycin (strA, strB, aadA and insertion sequence IS1133) and tetracycline (tetB, tetM and tetW) resistance elements in plant and soil samples. The qPCR were reproducible and consistent whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Molecular tools, such as PCR and quantitative real-time PCR, have been developed for many ARGs (Heuer and Smalla, 2007;Walsh et al, 2011). A limited number of studies have applied molecular methods to aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular tools, such as PCR and quantitative real-time PCR, have been developed for many ARGs (Heuer and Smalla, 2007;Walsh et al, 2011). A limited number of studies have applied molecular methods to aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Valuable insight into the manure resistomes of pigs, cattle, and chickens has been gained from direct culturing of antibiotic-resistant bacteria (10, 16, 17), quantitative PCR (qPCR) amplification of AR genes (5, 1820), and the exogenous isolation of plasmids carrying AR genes (21, 22). These approaches have shown that animal microbiomes are a substantial source of AR genes, especially of those conferring resistance to tetracycline and sulfonamide, which are often carried on plasmids (18, 2126).…”
Section: Introductionmentioning
confidence: 99%
“…Relative quantification using the ⌬⌬C T method is the most common method used in gene expression analysis (48) but has also been applied in environmental microbiology (51). The method determines the gene expression ratio (or abundance ratio) of a target gene in a sample compared to a control, normalizing with the expression ratio of a reference gene.…”
mentioning
confidence: 99%